High temperature acidizing diverter and method of making
Patent Information
- Application Number
- CN202610999344.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-07
- Publication Date
- 2026-10-13
AI Technical Summary
一方面,松香类等大分子树脂在常温强酸基液中的水溶性差,直接加入很难均匀分散,容易发生团聚
1、本方案预先将顺丁烯二酸改性松香酯与脂肪醇聚氧乙烯醚混合制成中间体,再加入到表面活性剂中。顺丁烯二酸改性松香酯含有三环二萜结构,存在较大的空间位阻,能够减缓表面活性剂碳链在高温环境下的热运动,防止结构收缩。因此体系在200℃下仍能保持一定的基础粘度;同时,在经历管柱泵送等高剪切作用导致粘度下降后,撤去剪切力时,该物质能促使打散的分子重新聚集,使液体粘度快速恢复到初始水平。
Smart Images

Figure CN122898263A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of chemicals for enhancing and modifying oil and gas field production, specifically to a high-temperature acidification diverting agent and its preparation method. Background Technology
[0002] Acidizing is an important method for enhancing the production of carbonate oil and gas reservoirs. In actual formations, due to the heterogeneity of the reservoir, injected acid tends to flow along high-permeability channels with lower resistance, resulting in low-permeability reservoirs not being effectively stimulated. To improve the distribution of acid across the rock profile, acidizing diverting agents are usually added. Currently, diverting agents based on viscoelastic surfactants are widely used in the field. Their mechanism of action is to utilize the reaction between acid and formation rocks to consume hydrogen ions. As the pH value increases, surfactant molecules self-assemble to form worm-like micelles, thereby increasing fluid viscosity, temporarily blocking high-permeability channels, and forcing subsequent acid to divert into low-permeability layers.
[0003] With the development of deep and ultra-deep oil and gas resources, reservoir temperatures are constantly rising. Conventional viscoelastic surfactants, when exposed to temperatures above 150°C or even 200°C, experience intensified thermal motion of their molecular chains, weakened internal non-covalent bonds, and a high susceptibility to micelle breakage and dehydration shrinkage. This leads to a significant decrease in the apparent viscosity of the fluid, and after the high-speed mechanical shearing during wellbore pumping, the fragmented molecular network is difficult to rebuild at high temperatures, thus losing its plugging and redirection capabilities.
[0004] To address the issue of viscosity reduction at high temperatures, researchers typically attempt to introduce rigid resin materials into surfactant systems for physical support or add metal crosslinking agents to construct chemical crosslinking networks. However, directly introducing these multi-component materials in actual preparation and application leads to serious engineering compatibility problems. On one hand, macromolecular resins such as rosin have poor water solubility in strong acid-based solutions at room temperature, making it difficult to disperse evenly and prone to agglomeration when added directly. On the other hand, zirconium carbonate is commonly used as a metal crosslinking agent in the field. When carbonates are directly added to high-concentration hydrochloric acid-based solutions, a large amount of carbon dioxide gas is rapidly generated, and the bubbles entrain the liquid, causing it to expand and easily leading to material overflow from the reactor. Furthermore, in strong acid solutions lacking buffers, free zirconium metal ions are prone to hydrolysis and precipitation. These compatibility and reaction control issues cause existing multi-component high-temperature diverting agents to frequently exhibit turbidity, stratification, and bottom solid precipitation during preparation and static storage. The products have poor physical stability and cannot meet the needs of large-scale construction and storage in oilfields. Summary of the Invention
[0005] To address the shortcomings of existing technologies, this invention provides a high-temperature acidification diverting agent and its preparation method, thus solving the problems.
[0006] To achieve the above objectives, the present invention provides the following technical solution: a high-temperature acidification reversing agent, made from components comprising the following parts by weight: 6-8 parts of erucamide propyl betaine; 4-6 parts of ethylene glycol; Sodium dodecylbenzenesulfonate 1-1.5 parts; Intermediate M2.5-4.5 parts; 78.5-85.7 parts of a 20% hydrochloric acid-based solution; Pre-solution Z 0.8-1.5 parts.
[0007] Preferably, the intermediate M is prepared by maleic acid modified rosin ester and fatty alcohol polyoxyethylene ether AEO-9 in a mass ratio of 3.5 to 4.5:1.
[0008] Preferably, the presolution Z is made of ammonium zirconium carbonate, ethylene glycol and hydrochloric acid with a mass fraction of 20%; the mass ratio of ammonium zirconium carbonate to ethylene glycol is 1:1.5 to 2.5; the mass of the hydrochloric acid with a mass fraction of 20% used in the presolution Z is 5%-6% of the mass of ammonium zirconium carbonate.
[0009] Preferably, the maleic acid modified rosin ester has an acid value of 180-210 mgKOH / g and a softening point of 130-145℃; the fatty alcohol polyoxyethylene ether AEO-9 has a hydrophilic-lipophilic balance value of 12.5-13.5 and an average relative molecular mass range of 580-600.
[0010] A method for preparing a high-temperature acidification diverting agent includes the following steps: Step 1: Add erucamide propyl betaine, ethylene glycol and sodium dodecylbenzene sulfonate to the preparation vessel according to the ratio, heat and stir to make the surfactant swell; Step 2: Add intermediate M into the preparation vessel, increase the stirring speed and maintain the shear reaction at a constant temperature to induce in-situ intercalation of the components; Step 3: After the reaction is complete, the system is cooled down, and 20% hydrochloric acid base solution and pre-solution Z are slowly injected into the preparation vessel in sequence. The mixture is stirred at low speed until it is homogeneous, and the high-temperature acidification diverting agent is obtained.
[0011] Preferably, the intermediate M added in step 2 is prepared through the following pretreatment steps: Maleic acid-modified rosin ester and fatty alcohol polyoxyethylene ether AEO-9 were added into a premixed reactor and carried out an association reaction under heating and stirring conditions. After the system was converted into a homogeneous, transparent, highly viscous fluid, it was cooled and collected to obtain the intermediate M.
[0012] Preferably, the presolution Z added in step 3 is prepared by the following pretreatment steps: Ammonium zirconium carbonate and ethylene glycol are mixed evenly in a preparation tank. Under stirring, 20% hydrochloric acid is slowly added dropwise to the preparation tank. The gas is vented and degassed. When the reaction is complete and no more gas is produced, the liquid is collected to obtain the pre-solution Z.
[0013] Preferably, in step 1, the temperature is raised to 45-55℃ and the stirring time is 45-60 minutes; in step 2, the stirring speed is increased to 300-400 rpm, the system temperature is controlled at 45-55℃, and the shear reaction time is maintained for 60-90 minutes.
[0014] Preferably, the stirring speed of the intermediate M pretreatment step is 150-250 rpm, the reaction temperature is 68-72℃, and the reaction time is 120-150 minutes.
[0015] Preferably, the stirring speed in the pre-solution Z pretreatment step is 100-150 rpm, and the dropping rate of hydrochloric acid with a mass fraction of 20% is 0.2-0.5 L / min; in step 3, the system is cooled to below 30°C, and the system temperature is monitored to not exceed 40°C during the injection of hydrochloric acid base solution.
[0016] This invention provides a high-temperature acidification reversing agent and its preparation method. It has the following beneficial effects: 1. In this scheme, maleic acid-modified rosin ester is first mixed with fatty alcohol polyoxyethylene ether to prepare an intermediate, which is then added to the surfactant. Maleic acid-modified rosin ester contains a tricyclic diterpene structure, exhibiting significant steric hindrance, which can slow down the thermal motion of the surfactant carbon chain under high-temperature conditions and prevent structural shrinkage. Therefore, the system can still maintain a certain basic viscosity at 200℃; simultaneously, after experiencing high shear forces such as column pumping that cause a decrease in viscosity, when the shear force is removed, this substance can promote the re-aggregation of dispersed molecules, allowing the liquid viscosity to quickly return to its initial level.
[0017] 2. Before adding ammonium zirconium carbonate, this method pre-degassing it with ethylene glycol and a small amount of hydrochloric acid. By consuming the carbonate ions and releasing carbon dioxide in advance, it avoids the generation of a large number of bubbles that would cause material overflow when directly adding the strong acid base liquid to the mixing tank. In addition, ethylene glycol acts as a buffer and dispersant in the system, preventing the hydrolysis and precipitation of zirconium ions in the strong acid environment, ensuring that the prepared reversing agent remains homogeneous and stable during static storage, without turbidity or precipitation.
[0018] 3. In the initial stage of construction, the viscosity of the highly acidic fluid is low, facilitating pumping into high-permeability cores of the formation. As the acid dissolves carbonate rocks, hydrogen ions are consumed, and the local pH value gradually increases. When the pH value rises above 3.0, zirconium ions and carboxyl groups in the system undergo multi-point coordination cross-linking, forming a network structure, which leads to a significant increase in fluid viscosity. The high-viscosity fluid generates significant flow resistance in the high-permeability pores, creating temporary blockage and forcing subsequent injected acid to change its flow direction and enter the low-permeability formation, thereby achieving uniform acidification of the heterogeneous reservoir. Attached Figure Description
[0019] Figure 1 This is a schematic diagram of the process steps of the present invention. Detailed Implementation
[0020] The technical solution of the present invention will now be clearly and completely described with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0021] The following detailed embodiments illustrate a high-temperature resistant acid-reversing agent and its preparation method according to the present invention. These embodiments are for illustrative purposes only and are not intended to limit the scope of protection of the invention. The main raw materials and reagents used in the following embodiments and comparative examples have the following sources and specifications; reagents not specifically mentioned are all commercially available analytical grade or higher products.
[0022] Erucamide propyl betaine (CAS No.: 149879-98-1) is an amphoteric surfactant with an active ingredient mass fraction of 30%±2% and a solid content of 35%-40%. In acidic aqueous solutions, this raw material forms worm-like micelles through hydrophobic association, providing basic viscoelasticity.
[0023] Maleic acid-modified rosin ester (CAS No.: 94581-15-4) is a polymer-modified resin with an acid value of 180 mg KOH / g-210 mg KOH / g and a softening point of 130℃-145℃. This component has a rigid tricyclic diterpenoid benzene ring structure and serves as a rigidity-reinforcing component to provide steric support within the micelles.
[0024] Fatty alcohol polyoxyethylene ether AEO-9 (CAS No.: 68131-39-5) is a synthetic polymer compound with a hydrophilic-lipophilic balance (HLB) value of 12.5-13.5 and an average relative molecular mass range of 580-600. Its polyoxyethylene segments are used to form hydrogen bonds with the carboxyl groups in maleic acid-modified rosin esters to construct supramolecular intermediates.
[0025] Ammonium zirconium carbonate (CAS No.: 68333-78-8) is an inorganic zirconium complex solution with a zirconium dioxide mass fraction of 15.0%-15.5%. This component acts as a pH-sensitive metal crosslinking agent, forming a coordination crosslinking network between zirconium ions and carboxyl groups within the system during acid reactions.
[0026] Sodium dodecylbenzenesulfonate (CAS No.: 25155-30-0), industrial grade, purity ≥90%. This component is used as a salt-resistant synergist to improve the structural stability of micelle systems under high temperature and high salt conditions.
[0027] Ethylene glycol (CAS No.: 107-21-1) and hydrochloric acid (CAS No.: 7647-01-0) are both commercially available industrial-grade products, used as a co-solvent and an acid base liquid, respectively.
[0028] Preparation Example 1: This preparation example provides a method for preparing rigid supramolecular intermediate M1, including the following steps: First, maleic acid-modified rosin ester and fatty alcohol polyoxyethylene ether AEO-9 were added to a premixing reactor at a mass ratio of 3.5:1. The stirring system was turned on and the speed was set to 150 rpm, and then the temperature was slowly increased to 68°C. Stirring was maintained at this temperature for 150 minutes until the materials in the reactor were fully associated, and the system was observed to transform into a uniform, transparent, amber-colored, highly viscous fluid. After heating was stopped, the temperature was cooled to below 40°C through circulating water at the bottom of the reactor, and the intermediate M1 was discharged.
[0029] Preparation Example 2: This preparation example provides a method for preparing the rigid supramolecular intermediate M2, including the following steps: Maleic acid-modified rosin ester and fatty alcohol polyoxyethylene ether AEO-9 were fed at a mass ratio of 4:1. The stirring device was started, and the speed was controlled at 200 rpm. The temperature inside the reactor was gradually increased to 70°C. Under this constant temperature condition, shearing treatment was continued for 135 minutes. After the solid particles in the reactor completely disappeared, forming a transparent and impurity-free high-viscosity liquid intermediate, it was naturally cooled to below 40°C, and intermediate M2 was collected.
[0030] Preparation Example 3: This preparation example provides a method for preparing the rigid supramolecular intermediate M3, including the following steps: Maleic acid-modified rosin ester and fatty alcohol polyoxyethylene ether AEO-9 were added to a premixing reactor at a mass ratio of 4.5:1. The system was heated to stabilize the temperature at 72°C under stirring at 250 rpm. Supramolecular association between the two components was induced by constant-temperature stirring for 120 minutes. Once the system became an amber-colored, transparent fluid with stable flowability, stirring and heating were stopped, and the mixture was cooled to room temperature to obtain intermediate M3.
[0031] Preparation Example 4: This preparation example provides a method for preparing a controlled degassing type zirconium complex presol Z1, including the following steps: Ammonium zirconium carbonate and ethylene glycol were mixed at a mass ratio of 1:1.5 and placed in a preparation tank equipped with a venting and pressure relief function. Under low-speed stirring at 100 rpm, 20% hydrochloric acid was slowly added dropwise using a feed pump. The addition amount was controlled to be 5% of the mass of the ammonium zirconium carbonate, and the dropping rate was 0.2 L / min. The bubbles were controlled to overflow smoothly. Once the liquid surface returned to calm and no more gas was generated, the acidic zirconium complex pre-solution Z1 was obtained.
[0032] Preparation Example 5: This preparation example provides a method for preparing a controlled degassing type zirconium complex presol Z2, including the following steps: Premix ammonium zirconium carbonate and ethylene glycol at a mass ratio of 1:2 until homogeneous, then start stirring and maintain a constant speed of 120 rpm. At room temperature, add 20% hydrochloric acid (5.5% of the mass of ammonium zirconium carbonate) to the container at a constant dropping rate of 0.35 L / min using a dropping funnel. Continuously monitor the release of bubbles. Once the reaction is complete and no more carbon dioxide is released, collect the liquid in the container to obtain pre-solution Z2.
[0033] Preparation Example 6: This preparation example provides a method for preparing a controlled degassing type zirconium complex presol Z3, including the following steps: First, ethylene glycol was added to the preparation tank, followed by ammonium zirconium carbonate at a mass ratio of 2.5:1. Stirring was then started at 150 rpm. Hydrochloric acid with a mass fraction of 20% was pumped in at a rate of 0.5 L / min, with the total mass of hydrochloric acid being 6% of the mass of ammonium zirconium carbonate. During the reaction, the foam height was observed using a level gauge. Once the gas was completely released and the system had transformed into a stable acidic complex solution, the pre-solution Z3 was discharged.
[0034] Example 1: This example provides a high-temperature acid-reversing agent resistant to 200℃ and its preparation method, including the following steps: Add 6.0% (w / w) of erucamide propyl betaine, 4.0% (w / w) of ethylene glycol, and 1.0% (w / w) of sodium dodecylbenzene sulfonate to a mixing vessel. Start stirring and heat to 45°C, circulating and stirring for 45 minutes to allow the surfactant to fully swell. Maintaining the vessel temperature, pump 2.5% (w / w) of intermediate M1 obtained in Preparation Example 1 into the vessel. Increase the stirring speed to 300 rpm and maintain the reaction at this temperature for 90 minutes. Then, start the chilled water circulation and, when the material cools to 25°C, slowly add 85.7% (w / w) of 20% hydrochloric acid-based solution. Finally, add 0.8% (w / w) of the pre-solution Z1 obtained in Preparation Example 4 and stir at low speed for 30 minutes to obtain the final diverting agent.
[0035] Example 2: This example provides a high-temperature acidification reversing agent resistant to 200℃ and its preparation method, including the following steps: 7.0% erucamide propyl betaine, 1.2% sodium dodecylbenzene sulfonate, and 5.0% ethylene glycol by mass fraction were added to an enamel-lined reactor. The stirring device was started, and the reactor temperature was controlled to rise to 50°C, with continuous mixing until the system was homogeneous. Under continuous stirring, 3.5% of intermediate M2 obtained in Preparation Example 2 was slowly injected into the reactor. The stirring speed was adjusted to 350 rpm, and the reactor was kept at a constant temperature of 50°C for 75 minutes to induce in-situ embedding of the rigid framework. The system was then cooled to 28°C, and 82.1% (by mass) of 20% hydrochloric acid-based solution was pumped in, while monitoring the reactor temperature to ensure it did not exceed 40°C. Finally, 1.2% of the pre-solution Z2 obtained in Preparation Example 5 was added, and the mixture was stirred at low speed until homogeneous to obtain the final diverting agent.
[0036] Example 3: This example provides a high-temperature acid-reversing agent resistant to 200℃ and its preparation method, including the following steps: First, 8.0% erucamide propyl betaine, 6.0% ethylene glycol, and 1.5% sodium dodecylbenzenesulfonate by mass fraction were mixed in the main reactor. The heating system was turned on to stabilize the reactor temperature at 55°C, and the mixture was stirred for 60 minutes. Then, 4.5% of intermediate M3 obtained in Preparation Example 3 was added to the reactor, and the stirring speed was increased to 400 rpm. The temperature was maintained at this high shear condition for 60 minutes. After the intermediate was fully distributed, the reactor temperature was cooled to below 30°C. 78.5% 20% hydrochloric acid-based solution was added to the reactor, and in the final stage, 1.5% of the pre-solution Z3 obtained in Preparation Example 6 was pumped in. The components were integrated by low-speed stirring for 30 minutes to obtain the finished diverting agent.
[0037] Example 4: This example provides a high-temperature acid-reversing agent resistant to 200℃ and its preparation method, including the following steps: In a reactor, 7.5% erucamide propyl betaine, 1.3% sodium dodecylbenzenesulfonate, and 4.5% ethylene glycol were first added. Stirring was started and the temperature was controlled at 52°C for homogenization for 50 minutes. Then, 4.0% of intermediate M2 obtained in Preparation Example 2 was added, and the reaction was carried out at 380 rpm for 80 minutes at this temperature. After the reaction, the material temperature was lowered to 26°C by circulating cooling water through a jacket. Then, 81.7% (w / w) of 20% hydrochloric acid-based solution and 1.0% (w / w) of pre-solution Z2 obtained in Preparation Example 5 were sequentially injected into the reactor. Low-speed stirring was maintained until the pH of the system stabilized below 0.5, yielding the final diverting agent.
[0038] Comparative Example 1: Compared with Example 2, the difference is that intermediate M2 obtained from Preparation Example 2 and presolution Z2 obtained from Preparation Example 5 were not added, and the missing mass was made up by 20% hydrochloric acid. All other aspects are the same.
[0039] This comparative example was designed to verify the viscosity decrease of a conventional single surfactant system at 200°C. The comparison demonstrates the actual technical effectiveness of this solution in maintaining the high-temperature viscosity of the system after incorporating maleic acid-modified rosin ester and zirconium carbonate as multiple components.
[0040] Comparative Example 2: Compared with Example 2, the difference is that the intermediate M2 prepared in Example 2 was not used. Instead, maleic acid modified rosin ester and fatty alcohol polyoxyethylene ether AEO-9 were directly added to the reactor in the second stage of Example 2. All other aspects were the same.
[0041] This comparative example was set up to verify the necessity of the intermediate pretreatment process. Adding raw materials directly to the main reaction system without heating and premixing results in ineffective binding and dispersion of the materials, leading to the precipitation of maleic acid-modified rosin ester, which cannot enter the surfactant aggregates to provide physical support.
[0042] Comparative Example 3: Compared with Example 2, the difference is that maleic acid-modified rosin ester was not added when preparing the intermediate, and the missing mass was made up by ethylene glycol. All other aspects are the same.
[0043] This comparative example was set up to verify the specific functions of maleic acid-modified rosin ester. Maleic acid-modified rosin ester possesses a tricyclic diterpene structure, which can create steric hindrance within the surfactant. The absence of this substance leads to dehydration and shrinkage of the surfactant aggregates at high temperatures, thereby causing a decrease in the overall viscosity of the system.
[0044] Comparative Example 4: Compared with Example 2, the difference is that the pre-solution Z2 obtained in Preparation Example 5 was not added, and the missing mass was made up by 20% hydrochloric acid. All other aspects are the same.
[0045] This comparative example was set up to verify the cross-linking and thickening mechanism of ammonium zirconium carbonate. When the reaction of acid with the rock causes the formation environment pH to rise to 3.0 to 4.0, the zirconium ions dissociated from ammonium zirconium carbonate undergo multi-site coordination with carboxyl groups in the system. The absence of ammonium zirconium carbonate prevents the system from producing the secondary thickening effect triggered by the increase in pH during the acidification reaction.
[0046] Comparative Example 5: Compared with Example 2, the difference is that the pre-solution Z2 of Preparation Example 5 was not used. Instead, an equal mass of ammonium zirconium carbonate raw material was directly added to the main reactor containing 20% hydrochloric acid. All other aspects were the same.
[0047] This comparative example was set up to verify the engineering significance of pre-degassing treatment of ammonium zirconium carbonate. Directly adding carbonates to a strong acid solution will rapidly generate a large amount of carbon dioxide, causing material overflow. At the same time, without the buffering and damping effect of ethylene glycol, zirconium ions are prone to hydrolysis and aggregation in a strong acid environment, losing their coordination activity in subsequent working conditions, resulting in an uneven product state.
[0048] Test Example 1: pH Response and Viscosity Change Test This test case primarily aims to determine the viscosity change of the diverting agent system as the pH value increases during a simulated acid-rock reaction. The specific experimental steps are as follows: Take 500 mL of each of the finished diverting agents prepared in Examples 1 to 4 and Comparative Example 4, and place them in polytetrafluoroethylene reaction vessels equipped with mechanical stirring devices and heating jackets.
[0049] The reaction vessel was heated and kept constant at 90°C, and the speed of the stirrer was controlled at 300 rpm to simulate the temperature and flow conditions of the initial construction environment of the formation.
[0050] Calcium carbonate powder with a mesh size of 200 was slowly added in batches to the reaction vessel, simulating the acid-rock reaction process in real geological formations by consuming the acid solution with calcium carbonate. The pH value of the liquid in the vessel was monitored and recorded in real time throughout the test using an acid-resistant high-temperature electrode pH meter.
[0051] When the pH value of the system rises to the five test points of 0.5, 1.5, 2.5, 3.5, and 4.5, the addition of calcium carbonate powder is temporarily stopped. The system is stirred at a constant temperature for 10 minutes to allow the internal chemical reaction to fully balance, and then 50 mL of sample is taken from the container.
[0052] The samples obtained at each pH point were quickly transferred into the sealed test chamber of the Hacker high-temperature and high-pressure rheometer. The rheometer test temperature was set to 90°C, and the test time was 170 seconds. -1 The material was continuously sheared at a fixed shear rate for 20 minutes, and the apparent viscosity value was read after the shearing stabilized.
[0053] Table 1. Apparent viscosity test results of each system under different pH conditions (unit: mPa·s)
[0054] According to the data in Table 1, the apparent viscosity of the samples from Examples 1 to 4 remained between 18.2 and 31.0 mPa·s during the pH range of 0.5 to 1.5. When the pH rose above 2.5, especially reaching 3.5, the apparent viscosity of each example increased significantly, ranging from 305.8 to 412.5 mPa·s. When the pH further increased to 4.5, the increase in viscosity slowed and tended to stabilize. The apparent viscosity of the sample in Comparative Example 4 increased only from 24.3 mPa·s to 58.7 mPa·s throughout the entire tested pH range.
[0055] In the acidic stage (pH less than 1.5), the system has a high hydrogen ion concentration. The carboxyl groups on the maleic acid-modified rosin ester exist in a protonated form, and the tetravalent zirconium ions released from the dissociation of ammonium zirconium carbonate are in a hydrated state. No coordination reaction occurs between the components, and the system exhibits a low apparent viscosity. As calcium carbonate consumes the acid, the pH rises to the 3.0-3.5 range. The carboxyl groups dissociate, releasing hydrogen ions, and the tetravalent zirconium ions regain their coordination ability. At this point, the tetravalent zirconium ions form multi-point coordination connections with the carboxyl groups in the system, forming a network structure within the system. This restricts the free flow of the fluid, leading to a significant increase in the apparent viscosity of the system.
[0056] Comparative Example 4 did not include a pre-solution of zirconium carbonate. Although the acid concentration decreased with increasing pH, the lack of zirconium metal ions capable of coordinating with carboxyl groups prevented the formation of a large-scale network cross-linked structure within the system, thus failing to produce a significant viscosity abrupt change. This verifies the role of zirconium carbonate in inducing a sudden viscosity change with increasing pH in this system.
[0057] Test Example 2: Observation of Macroscopic Physical State and Process Stability This test example is used to determine the gas release of each system during the initial preparation stage and its physical stability under long-term static conditions. The specific experimental steps are as follows: In the final feeding step of Examples 2, 2, and 5, a 500mL open glass graduated cylinder marked with a volume scale was used as the reaction endpoint container. The maximum foam expansion volume caused by the escape of internal gas within 3 minutes after the materials were added was recorded.
[0058] After the initial foam has completely subsided, 100 mL of liquid sample was taken from each of the three groups and transferred to a 250 mL transparent graduated cylinder with a ground glass stopper and sealed. Two parallel samples were prepared for each group.
[0059] Place one set of graduated cylinders in a dark indoor environment at 25℃ and store it still, while place the other set in a constant temperature drying oven set at 70℃.
[0060] Regularly observe and record the macroscopic state of the liquid in the graduated cylinder. After 24 hours of settling, observe the clarity of the liquid and whether there is any stratification. After 168 hours of settling, read the volume of the solid precipitate at the bottom of the graduated cylinder.
[0061] Table 2. Macroscopic state test results of each system under static conditions at different temperatures.
[0062] According to the data in Table 2, in Example 2, the foam expansion volume at the end of the feeding stage was 4.2 mL. After standing for 168 hours at 25°C and 70°C, no solid sediment appeared at the bottom, and the liquid remained homogeneous and transparent. In Comparative Example 5, the foam expansion volume reached 247.6 mL during the final feeding step, resulting in material overflow, and a small amount of sediment was produced after standing for 168 hours. In Comparative Example 2, the initial foaming amount was within the normal range, but the liquid became cloudy after standing at a constant temperature for 24 hours. After 168 hours at 70°C, the bottom sediment volume reached 16.5 mL, indicating that internal substances had separated and precipitated.
[0063] The above test data reflects the mechanism by which the intermediate pretreatment process and the pre-degassing process of ammonium zirconium carbonate in this scheme maintain the physical stability of the system. In Comparative Example 5, ammonium zirconium carbonate was directly added to a liquid containing 20% hydrochloric acid. The carbonate ions reacted rapidly with the strong acid, and the resulting carbon dioxide gas could not be discharged in time in the viscous fluid, causing a large amount of liquid to be entrained by the gas, forming expanding foam. Without the use of ethylene glycol for pre-dispersion and buffering, some zirconium ions underwent hydrolysis and precipitation in the strong acid environment, resulting in zirconium-containing solid precipitate forming in Comparative Example 5 after standing, and the product state was uneven.
[0064] In Comparative Example 2, the maleic acid-modified rosin ester was added directly to the main reaction system without pretreatment. Maleic acid-modified rosin ester has poor water solubility at room temperature, and without a specific temperature-controlled thermal mixing process with fatty alcohol polyoxyethylene ether, the two components cannot form a bonded state through intermolecular hydrogen bonds. The directly added maleic acid-modified rosin ester molecules cannot enter and stably exist within the surfactant aggregates. During the standing process, under the influence of gravity and temperature, the undispersed resin molecules aggregate, leading to liquid turbidity and precipitation.
[0065] Example 2, by conducting a controlled reaction of ammonium zirconium carbonate with dilute acid in ethylene glycol, pre-consumed most of the carbonate ions, pre-emptively initiated the bubble generation process, thus avoiding material overflow issues during acid addition in the main reactor. Simultaneously, the pre-prepared intermediate ensured the maleic acid-modified rosin ester remained dispersed in the surfactant system, preventing precipitation and stratification during later storage. This demonstrates the practical effectiveness of this pretreatment step in ensuring the long-term physical stability of the fluid.
[0066] Test Example 3: Heating Rheological Properties and Temperature Limit Test at 200℃ This test example is used to determine the apparent viscosity change of the cross-linked system during continuous heating, and to test its viscosity retention ability at a high temperature of 200℃. The specific experimental steps are as follows: Take 200 mL of each of the liquid samples from Examples 1 to 4, Comparative Examples 1 and 3, and place them into beakers. Add calcium carbonate powder to each beaker in batches while stirring continuously. Use a pH meter to monitor the pH value of the liquid and adjust the pH value of each group of samples to between 3.5 and 3.8 to bring the system to a high viscosity state after cross-linking.
[0067] Take 50 mL from each group of samples with adjusted pH values and transfer them sequentially into the high-temperature and high-pressure coaxial cylindrical test cup of the Hacker rheometer, then seal the test cup.
[0068] Turn on the rheometer pressurization system and fill the sealed test cup with 3.5 MPa of nitrogen gas as back pressure to prevent the test liquid from boiling and vaporizing during high-temperature heating.
[0069] Start the rheometer and set the rotor's constant shear rate to 170 s. -1 Turn on the heating program and set the heating rate of the heating panel to 3℃ / min, so that the temperature inside the test cup can be continuously increased from 25℃ to 200℃.
[0070] Record the apparent viscosity values throughout the entire heating cycle, and extract the specific rheological data of each sample at three temperature points: 150℃, 180℃, and 200℃.
[0071] Table 3. Apparent viscosity test results of different systems during the heating process (unit: mPa·s)
[0072] According to the data in Table 3, the apparent viscosity of the samples from Examples 1 to 4 remained between 124.6 and 168.7 mPa·s when heated to 150°C; and remained between 38.5 and 52.8 mPa·s when the temperature rose to 200°C. The apparent viscosity of Comparative Example 1 decreased to 15.4 mPa·s at 150°C and was only 2.1 mPa·s at 200°C. The viscosity of the sample from Comparative Example 3 was 43.8 mPa·s at 150°C, decreasing to 8.9 mPa·s at 200°C.
[0073] As temperature increases, the thermal motion of surfactant molecules intensifies, and the non-covalent bonds between molecules weaken. This physical change leads to alterations in the morphology of surfactant aggregates, with microstructure shrinking or breaking down, macroscopically manifesting as a significant decrease in the apparent viscosity of the fluid. Comparative Example 1, composed of only a single surfactant, lacks substances and connecting networks capable of resisting high-temperature thermal motion; therefore, it exhibits the greatest viscosity decrease under high-temperature conditions, essentially losing viscosity at 200°C.
[0074] Maleic acid-modified rosin ester contains a tricyclic diterpene structure, and its molecules exhibit significant steric hindrance. In Examples 1 to 4, the maleic acid-modified rosin ester is distributed within the surfactant aggregates, and its steric hindrance restricts the intense thermal motion of the surfactant carbon chains at high temperatures. Simultaneously, the coordination network formed by the zirconium ions and carboxyl groups on the outer side maintains the structural integrity of the aggregates at high temperatures. In Comparative Example 3, although ammonium zirconium carbonate for crosslinking was added, maleic acid-modified rosin ester was not added. At 200°C, the external crosslinking network alone could not prevent the deformation and dehydration shrinkage of the internal structure of the surfactant due to thermal motion, resulting in the apparent viscosity of Comparative Example 3 not being effectively maintained at high temperatures. This indicates that the spatial structure of the maleic acid-modified rosin ester plays a major role in the system's tolerance to 200°C.
[0075] Test Example 4: Viscosity Recovery Performance Test under Variable Shear Rate This test example is used to determine the viscosity rebuilding rate of a system after undergoing high-speed shearing and returning to a low-shear state, simulating the process of a liquid undergoing shear viscosity reduction within a construction tubing and recovering its viscosity after entering the formation. The specific experimental steps are as follows: Take 200 mL of each of the liquid samples prepared in Examples 1 to 4 and Comparative Example 1, add calcium carbonate powder to adjust the pH value of the liquid to between 3.5 and 3.8, so that the sample to be tested is in a cross-linked and thickened state.
[0076] Take 50 mL of each sample and put it into the pressure test tube of the Hacker rheometer. Pressurize it with nitrogen gas at 3.5 MPa and raise the test temperature of the rheometer to 150 °C and maintain it.
[0077] The initial shear rate of the rheometer rotor was set to 170 s. -1 Run continuously for 20 minutes, and record the stable apparent viscosity at this time as the initial viscosity reference value.
[0078] The shear rate was instantly increased to 1000s. -1 The liquid was kept in this high-speed shear state for 15 minutes, and the apparent viscosity value at the end of the shearing was recorded to observe the viscosity reduction of the liquid under strong mechanical shear force.
[0079] The shear rate was instantly adjusted back to 170s. -1 The apparent viscosity recovery curve of the liquid was continuously recorded, and the time required for the viscosity to recover to 90% of the initial reference value was calculated and recorded.
[0080] Table 4. Viscosity recovery test results of different systems under varying shear rates.
[0081] According to the data in Table 4, at a test temperature of 150°C, Examples 1 to 4 were completed in 170 seconds. -1 The initial apparent viscosity was measured to be 122.4 to 165.2 mPa·s at shear rates of [missing value]. When the shear rate was increased to 1000 s⁻¹, [missing value]. -1 At that time, the apparent viscosity of each embodiment rapidly decreased to 18.3 to 28.1 mPa·s. The shear rate recovered to 170 s⁻¹. -1 Subsequently, in Examples 1 to 4, the viscosity recovered to over 90% of its initial viscosity within 2.4 to 3.2 minutes. The initial viscosity of Comparative Example 1 was 15.8 mPa·s, and it recovered to over 90% of its initial viscosity within 1000 s. -1 The shear rate decreased to 1.2 mPa·s, and when the shear rate returned to 170 s⁻¹ -1 After 30 minutes of continuous monitoring, the viscosity of Comparative Example 1 did not show a significant increase and could not be restored to the initial level.
[0082] When a fluid is subjected to high-speed mechanical shearing, the internal molecular alignment is forced to conform to the flow field direction, causing deformation of surfactant aggregates. Non-covalent bonds are broken by external physical forces, macroscopically manifesting as a significant decrease in viscosity. Comparative Example 1, containing only a single surfactant component, experienced complete destruction of its aggregate structure under the combined effects of a high-temperature environment (150°C) and high-speed shearing. After the high shear force was removed, the surfactant molecules struggled to rearrange and aggregate due to the intense thermal motion of molecules at high temperatures, resulting in the system losing its viscosity recovery capability.
[0083] In Examples 1 to 4, maleic acid-modified rosin ester and ammonium zirconium carbonate were introduced into the formulations. After the shear rate decreased, the tricyclic diterpenoid structure in the maleic acid-modified rosin ester molecule exhibited strong hydrophobicity and steric hindrance, enabling the dispersed surfactant molecules to rapidly re-aggregate around the rosin ester core. Simultaneously, the coordination bond formed between zirconium ions and carboxyl groups is a dynamic and reversible connection. When the mechanical force weakens, the free metal ions and carboxyl groups spontaneously re-coordinate under thermodynamic drive.
[0084] Through the combined action of internal hydrophobic association and external dynamic coordination cross-linking, the structural network damaged by shearing can be rapidly rebuilt in a short time, allowing the macroscopic viscosity of the fluid to return to its original level within minutes. This characteristic ensures that the working fluid retains sufficient viscosity properties when entering the formation after passing through high-shear stages such as wellbore pumping.
[0085] Test Example 5: Physical Simulation Displacement Test of Two-Tube Parallel Core This test example is used to determine the flow diversion performance of a crosslinked system under high temperature and heterogeneous core conditions. The specific experimental steps are as follows: Natural carbonate rock cores were selected and subjected to oil washing and drying. Gas permeability was measured from the cores, and cores with permeability ranging from 145 to 155 mD were selected as high-permeability cores, while those with permeability ranging from 14 to 16 mD were selected as low-permeability cores. High-permeability and low-permeability cores were used in pairs, with a permeability difference maintained at approximately 10 times.
[0086] The paired high-permeability and low-permeability cores were respectively loaded into the two holders of the dual-tube parallel displacement device. A constant annular pressure of 15.0 MPa was applied to the holders. The heating system of the constant temperature chamber was turned on to heat the holders and the internal cores to 180°C and maintain the temperature.
[0087] Turn on the horizontal flow pump and inject a 2% potassium chloride solution into the parallel core at a constant flow rate of 2.0 mL / min. After the system pressure and the flow rates at both outlets stabilize, record the injection pressure at this time. Use a graduated cylinder to collect the discharge volume at the high-permeability end and the low-permeability end over 5 minutes, and calculate the influent diversion rate of the low-permeability core during the water drive stage.
[0088] The injection fluid of the advection pump was switched to the liquid sample prepared in Example 2 and Comparative Example 1, and acid was continuously injected into both cores simultaneously at a flow rate of 2.0 mL / min. The highest injection pressure during the acid injection process was recorded in real time by a pressure sensor on the pipeline.
[0089] During acid injection, the effluent from both the high-permeability and low-permeability core ends was continuously collected. Pumping was stopped when the total injected volume reached three times the core pore volume. The percentage of total influent to total effluent from the low-permeability core during the acid displacement stage was measured and calculated.
[0090] Table 5. Results of Parallel Core Simulation Displacement Tests in Examples and Comparative Examples
[0091] According to the data in Table 5, during the 2% potassium chloride solution water flooding stage before acid injection, due to the approximately 10-fold permeability difference between the high-permeability and low-permeability cores, most of the fluid in both Example 2 and Comparative Example 1 tests entered the high-permeability core, with the low-permeability core diversion rates being only 8.6% and 9.1%, respectively. After switching to injecting the Example 2 sample, the system's maximum injection pressure increased to 18.4 MPa, and the fluid diversion rate of the low-permeability core increased to 42.7%. When switching to injecting the Comparative Example 1 sample, the system's maximum injection pressure was only 2.7 MPa, and the fluid diversion rate of the low-permeability core decreased to 6.5%.
[0092] When fluids flow in porous media, there are resistance differences, and liquids preferentially enter channels with high permeability and low resistance. Comparative Example 1 contains only a single component, erucic acid-amylacetic betaine. Under a high-temperature environment of 180°C, the acid solution enters the high-permeability core and dissolves the carbonate rock. Although the pH value inside the core pores increases, the system lacks an effective metal coordination mechanism and a temperature-resistant component, and therefore cannot significantly increase the fluid viscosity to generate sufficient flow resistance.
[0093] Meanwhile, the acid dissolution process further enlarged the pore channels within the high-permeability core. The injected fluid continued to flow out along the high-permeability channels with decreasing resistance, failing to divert into the low-permeability core, resulting in a decrease in the diversion rate at the low-permeability end.
[0094] In Example 2, pretreated maleic acid-modified rosin ester and zirconium carbonate were added to the sample. When the acid preferentially entered the high-permeability core, it reacted with calcium carbonate, resulting in a decrease in the local acidity. At 180°C, the released tetravalent zirconium ions rapidly underwent multi-site coordination reactions with the carboxyl groups on the maleic acid-modified rosin ester and surfactant molecules.
[0095] The tricyclic diterpenoid structure of maleic acid-modified rosin ester provides steric hindrance to resist high-temperature thermal motion. Combined with the internal coordination network, this rapidly increases the viscosity of the fluid within the core pores. The high-viscosity fluid generates a flow resistance of up to 18.4 MPa in the high-permeability channels. This resistance forces subsequently injected liquid samples to change their flow path and enter the relatively low-permeability core for acidification and dissolution, increasing the proportion of fluid entering the low-permeability layer. This test data confirms the effectiveness of this formulation in achieving physical diversion in heterogeneous reservoirs through chemical coordination and steric hindrance mechanisms.
[0096] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.
Claims
1. A high-temperature acidification diverting agent, characterized in that, Made from components comprising the following parts by weight: 6-8 parts of erucamide propyl betaine; 4-6 parts ethylene glycol; Sodium dodecylbenzenesulfonate 1-1.5 parts; Intermediate M2.5-4.5 parts; 78.5-85.7 parts of a 20% hydrochloric acid-based solution; Pre-solution Z 0.8-1.5 parts.
2. The high-temperature acidification diverting agent according to claim 1, characterized in that: The intermediate M is prepared by maleic acid-modified rosin ester and fatty alcohol polyoxyethylene ether AEO-9 in a mass ratio of 3.5 to 4.5:
1.
3. The high-temperature acidification diverting agent according to claim 1, characterized in that: The presolution Z is made of ammonium zirconium carbonate, ethylene glycol and 20% hydrochloric acid by mass; the mass ratio of ammonium zirconium carbonate to ethylene glycol is 1:1.5 to 2.5; the mass of the 20% hydrochloric acid used in the presolution Z is 5%-6% of the mass of the ammonium zirconium carbonate.
4. The high-temperature acidification diverting agent according to claim 2, characterized in that: The maleic acid-modified rosin ester has an acid value of 180-210 mgKOH / g and a softening point of 130-145℃; the fatty alcohol polyoxyethylene ether AEO-9 has a hydrophilic-lipophilic balance value of 12.5-13.5 and an average relative molecular mass range of 580-600.
5. A method for preparing a high-temperature acidizing diverting agent, wherein the high-temperature acidizing diverting agent according to any one of claims 1-4 is characterized in that, Includes the following steps: Step 1: Add erucamide propyl betaine, ethylene glycol and sodium dodecylbenzene sulfonate to the preparation vessel according to the ratio, heat and stir to make the surfactant swell; Step 2: Add intermediate M into the preparation vessel, increase the stirring speed and maintain the shear reaction at a constant temperature to induce in-situ intercalation of the components; Step 3: After the reaction is complete, the system is cooled down, and 20% hydrochloric acid base solution and pre-solution Z are slowly injected into the preparation vessel in sequence. The mixture is stirred at low speed until it is homogeneous, and the high-temperature acidification diverting agent is obtained.
6. The method for preparing a high-temperature acidification diverting agent according to claim 5, characterized in that: The intermediate M added in step 2 is prepared through the following pretreatment steps: Maleic acid-modified rosin ester and fatty alcohol polyoxyethylene ether AEO-9 were added into a premixed reactor and carried out an association reaction under heating and stirring conditions. After the system was converted into a homogeneous, transparent, highly viscous fluid, it was cooled and collected to obtain the intermediate M.
7. The method for preparing a high-temperature acidification diverting agent according to claim 5, characterized in that: The presolution Z added in step 3 is prepared through the following pretreatment steps: Ammonium zirconium carbonate and ethylene glycol are mixed evenly in a preparation tank. Under stirring, 20% hydrochloric acid is slowly added dropwise to the preparation tank. The gas is vented and degassed. When the reaction is complete and no more gas is produced, the liquid is collected to obtain the pre-solution Z.
8. The method for preparing a high-temperature acidification diverting agent according to claim 5, characterized in that: In step 1, the temperature is raised to 45-55℃ and the stirring time is 45-60 minutes; in step 2, the stirring speed is increased to 300-400 rpm, the system temperature is controlled at 45-55℃, and the shear reaction time is maintained for 60-90 minutes.
9. The method for preparing a high-temperature acidification diverting agent according to claim 6, characterized in that: The stirring speed for the pretreatment step of intermediate M is 150-250 rpm, the reaction temperature is 68-72℃, and the reaction time is 120-150 minutes.
10. The method for preparing a high-temperature acidification diverting agent according to claim 7, characterized in that: The stirring speed in the pretreatment step Z is 100-150 rpm, and the dropping rate of 20% hydrochloric acid is 0.2-0.5 L / min. In step 3, the system is cooled to below 30°C, and the system temperature is monitored to not exceed 40°C during the injection of hydrochloric acid base solution.